The Effect of Inclines on Joint Angles in Stroke Survivors During Treadmill Walking - Zhang, Xin; Lu, Yanting; Chien, Jung Hung; Fu, Chenlei; Zhou, Zhe; Li, Hua; Hu, Gongwei; Sun, Tianbao (Frontiers in Neurology, 2022)
Stroke severely affects the quality of life, specifically in walking independently. Thus, it is crucial to understand the impaired gait pattern. This gait pattern has been widely investigated when walking on a level treadmill. However, knowledge about the gait pattern when walking on inclines is scarce. Therefore, this study attempted to fulfill this knowledge gap. In the current study, fifteen stroke survivors and fifteen age-/height-/weight healthy controls were recruited. Participants were instructed to walk on three different inclines: 0°, 3°, and 6°. Participants were required to walk on each incline for two minutes and needed to complete each incline two times. The dependent variables were peaks values for ankle/knee/hip joint angles and the respective variability of these peak values. The results found that an increment of the incline significantly increased the peak of hip flexion and the peak of knee flexion but did not affect the peak values of ankle joints in the paretic leg in these stroke survivors. In comparison with healthy controls, lower hip extension, lower hip flexion, lower knee flexion, and lower ankle plantar flexion were observed in stroke survivors. A clinical application of this work might assist physical therapists in building an effective treadmill training protocol.